2019
DOI: 10.1017/s0007114519001855
|View full text |Cite
|
Sign up to set email alerts
|

The effect of l-arginine supplementation on lipid profile: a systematic review and meta-analysis of randomised controlled trials

Abstract: A number of clinical trials have examined the effect of l-arginine on lipid profile in recent years; however, the results remain equivocal. Therefore, the present study aims to summarise and quantitatively examine the available evidence on the effectiveness l-arginine supplementation on lipid parameters using a systematic review and meta-analytic approach. Online databases including PubMed, Scopus, ISI Web of Science, Cochrane Library and Google Scholar were searched up to April 2019 for randomised controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 57 publications
(186 reference statements)
0
12
0
1
Order By: Relevance
“…It has been suggested that administration of L-citrulline instead of L-arginine to increase systemic L-arginine levels might be advantageous because it escapes metabolism by gut bacteria and liver arginase (Solomonson et al, 2003). Clinical trials in CVD have shown diverging results, and there is currently not enough evidence to support L-arginine substitution (Bednarz et al, 2005;Hadi et al, 2019). Other dietary means to support NOS output in CVD have been proposed, where administration of the BH4 precursors folate or sepiapterin has been tested in small clinical trials, but data are inconclusive and larger trials are needed to clarify any beneficial role of BH4 analogs (De Maria et al, 2014;Gori et al, 2001).…”
Section: Dietary Aspectsmentioning
confidence: 99%
“…It has been suggested that administration of L-citrulline instead of L-arginine to increase systemic L-arginine levels might be advantageous because it escapes metabolism by gut bacteria and liver arginase (Solomonson et al, 2003). Clinical trials in CVD have shown diverging results, and there is currently not enough evidence to support L-arginine substitution (Bednarz et al, 2005;Hadi et al, 2019). Other dietary means to support NOS output in CVD have been proposed, where administration of the BH4 precursors folate or sepiapterin has been tested in small clinical trials, but data are inconclusive and larger trials are needed to clarify any beneficial role of BH4 analogs (De Maria et al, 2014;Gori et al, 2001).…”
Section: Dietary Aspectsmentioning
confidence: 99%
“…To test the hypothesis that hepatocyte arginine catabolism enhances hepatic and peripheral energy metabolism apart from ARG2 upregulation, and apart from ARG2 products ornithine and urea, we expressed arcA in hepatocytes. arcA encodes a high-affinity arginine deiminase 23 that differs from the arginases in its enzymatic products, citrulline and ammonia. 22 We delivered arcA or eGFP (an ectopic expression control vector) via tail-vein injection of AAV8 encoding arcA or eGFP under hepatocyte-specific thyroxine binding globulin promoter control in 5-week-old db/db mice.…”
Section: Resultsmentioning
confidence: 99%
“…The current evidence does not suggest obvious deleterious metabolic effects of chronic arginine deprivation. Similarly, data on effects of long-term L-arginine supplementation are conflicting in both pre-clinical and clinical studies, 23 , 55 , 56 , 57 , 58 Taken together, the data do not reveal negative metabolic sequelae from chronic modulation of nitrogen status. What is clear is the net metabolic benefit at least of short-term arginine manipulation.…”
Section: Discussionmentioning
confidence: 98%
“…Our results did not, however, confirm the significant differences in the triglycerides or cholesterol ratio, and the total, LDL, and HDL levels were higher in the l -arginine-treated group. Although there are currently no definitive conclusions for l -arginine supplementation on improving lipid profile [ 43 ], several experimental and clinical reports showed that l -arginine might exert positive effects on the lipid profile in rats and humans [ 44 , 45 , 46 ]. The discrepancies in our results and other findings may conceivably be attributed to the supplementation dosage and the differences in duration, as probably more time (4 weeks) is needed to detect changes in the systemic lipid status.…”
Section: Discussionmentioning
confidence: 99%